2015
DOI: 10.7314/apjcp.2015.16.16.7321
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Spiritual Health and Quality of Life in Patients with Cancer

Abstract: As the essence of health in humans, spiritual health is a fundamental concept for discussing chronic diseases such as cancer and a major approach for improving quality of life in patients is through creating meaningfulness and purpose. The present descriptive analytical study was conducted to assess the relationship between spiritual health and quality of life in 210 patients with cancer admitted to the Cancer Institute of Iran, selected through convenience sampling in 2014. Data were collected using Spiritual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 32 publications
3
13
0
4
Order By: Relevance
“…Pain/ discomfort was the most frequently reported problems. It agreed with the result of the study by Mohebbifar et al, (2015), which showed pain to be one of the poor quality of life signs and symptoms, while the physical function was the second functional status of the quality of life in cancer patients. These findings were also similar to what was found by the previous study in France.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Pain/ discomfort was the most frequently reported problems. It agreed with the result of the study by Mohebbifar et al, (2015), which showed pain to be one of the poor quality of life signs and symptoms, while the physical function was the second functional status of the quality of life in cancer patients. These findings were also similar to what was found by the previous study in France.…”
Section: Discussionsupporting
confidence: 91%
“…Unfortunately, the study did not identify the reason for the differences between nationalities. Mohebbifar et al, (2015) stated that spiritual health should be a factor that improves HRQoL patients with cancer, so a combination of care therapies and spiritual interventions is a priority in cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its fatality, patients living with CA struggle with a sense that their lives are threatened in meaning and purpose (Canada et al, 2016; Weathers et al, 2016). In other words, patients experience existential suffering, specific to individuals and depending on the personal meaning of the disease (Wang et al, 2017), leading to the loss of self-esteem and faith (Mohebbifar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, CA has a substantial negative impact on a person's spiritual well-being (SpWB) and quality of life (QoL). SpWB is a fundamental approach for improving QoL in patients through creating meaningfulness and purpose (Mohebbifar et al, 2015), by way of improving physical and mental health outcomes as well as the maintenance of social roles and relationships during the CA experience (Salsman et al, 2015). This is because spirituality is the dynamic and intrinsic dimension of human life that relates to the way persons experience, express, and/or seek meaning, purpose, and transcendence, and the way they connect to the moment, to self, to others, to nature, to the significant and/or the sacred (Puchalski et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Religious health is the satisfaction that comes from being associated with God, and the existential health is defined as attempts to understand the meaning and purpose of life and obtain satisfaction from it. [ 1 2 ]…”
Section: Introductionmentioning
confidence: 99%